Types of Evidentiality in Turkic, Iranian And Neighbouring Languages (Türk, İran ve Komşu Dillerde Evidensiyellik Tipleri) Kollokyumu - Arıözçelik, Mehmet (İlim Yayma Cemiyeti, 1998)
[No Abstract Available]